2014
DOI: 10.1097/icb.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Retinal Detachment in Werner Syndrome

Abstract: Vitreoretinal changes found in this case might have been partially because of the premature aging associated with Werner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, there have been no data obtained by an extensive literature screening on the incidence of dyslipidemia and characteristics of dyslipidemia/fatty liver in Werner syndrome patients. To address this issue in the current edition of the guidelines, we screened cases reported on PubMed and Medical Online from 1996 to 2016 (98 articles, 119 cases), from which 44 cases (26 men with a mean age of 45.6 years) including some descriptions or data relating to either lipid or fatty liver in the articles were selected for analysis (reports before 2005: 26 cases) 8–43 . The detailed literature search method and process were as follows.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no data obtained by an extensive literature screening on the incidence of dyslipidemia and characteristics of dyslipidemia/fatty liver in Werner syndrome patients. To address this issue in the current edition of the guidelines, we screened cases reported on PubMed and Medical Online from 1996 to 2016 (98 articles, 119 cases), from which 44 cases (26 men with a mean age of 45.6 years) including some descriptions or data relating to either lipid or fatty liver in the articles were selected for analysis (reports before 2005: 26 cases) 8–43 . The detailed literature search method and process were as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of components of DNA replication machinery, DNA damage signaling pathways ( Frappart et al, 2005 ; Lee et al, 2012a , b ) as well as DNA repair factors ( Lee et al, 2000 ; Frappart and McKinnon, 2007 , 2008 ; Baranes et al, 2009 ) revealed different levels of CNS malformations. In contrast, even though congenital disorders caused by mutations in DDR genes exhibit retinal malformations ( Lim and Wong, 1973 ; Erdöl et al, 2003 ; Bhisitkul and Rizen, 2004 ; Chai et al, 2009 ; Krzyżanowska-Berkowska et al, 2014 ; Sasoh et al, 2014 ), the impact of defective DDR in retinogenesis and visual impairment still awaits investigation. Studies about the DNA damage signaling and repair factors revealed optic nerve morphological alterations in Nbn -deficient retinas, but loss of NBN and ATM did not impact retinal neurogenesis ( Baranes et al, 2009 ; Rodrigues et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of eye-related complications, the positive rate of cataracts is 100% (with a 96% positive rate for cataracts in both eyes) [ 7 ]. Certain reports exist of patients with Werner syndrome with cystoid macular edema [ 8 , 9 ], bilateral retinal detachment [ 10 ], or primary bullous keratopathy [ 11 ]; however, few reports have documented the changes in the thickness of the retina and choroid. In healthy people, aging causes thinning of the retina and choroid [ 12 , 13 ] and similar changes are speculated to occur in patients with Werner syndrome.…”
Section: Introductionmentioning
confidence: 99%